Education Outreach and Public Engagement - Dolan, Erin.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2008)
Mentoring in Academia and Industry Series Editor: J. Ellis Bell Biology is evolving rapidly, with more and more discoveries arising from interaction with other disciplines such as chemistry, mathematics, and computer science. Undergraduate and Graduate biology education is having a hard time keeping up. To address this challenge, this bold and innovative series will assist science education programs at research universities, four-year colleges and community colleges across the country and by enriching science teaching and mentoring of both students and faculty in academia and for industry representatives. The series aims to promote the progress of scientific research and education by providing guidelines for improving academic and career building skills for a broad audience of students, teachers, mentors, researchers, industry, and more. Volume 1 Education Outreach and Public Engagement Edited by Erin Dolan Whether you are at a land-grant institution with an articulated mission to translate research to the public or your child’s second grade class is studying butterfly development, there are a whole host of reasons to get involved in public education about science. University expectations for promotion and tenure and recent mandates from federal agencies are requiring that scientists engage the public in a meaningful way. Yet, most scientists receive little if any preparation about how to do this. The programs, tools, and resources featured in this monograph will assist scientists and scientists-in-training in enhancing public awareness and understanding of science and considering its applications and implications. In addition, this monograph addresses the notion that public engagement goes beyond enhancing the layperson’s comprehension of science to engaging the public in real and meaningful dialogue about science.
Why? Identifying the Impetus for K-12 Outreach and Engagement -- Who and What? Defining the Scope of K-12 Outreach and Engagement -- How? Developing the Plan and Making it Happen -- How Well? Evaluating K-12 Outreach and Engagement -- Sharing the News.
Keywords: Learning; Instruction; Teaching; Life sciences; Learning & Instruction; Teaching and Teacher Education; Life Sciences, general